The Micro, Macro-Nutritional and Pharmacological Potential of Coelogyne suaveolens Root and Bulb Extracts: A Comprehensive in-vitro, in-vivo and in-silico Assessment - Islam, Saidul; Chowdhury, Md. Tanvir; Younus, Sabrina; Kader, Md Anower; Polash, Shajjad Hossain; Nur, Md. Arifuzzaman; Mamun, Md. Al; Joydhar, Prince; Hossen, S. M. Moazzem (Iraqi Journal of Science, 2026)
The medicinal potential of an orchid Coelogyne suaveolens, subjecting the ethyl acetate fraction of the acetonic extract from its root and bulb to various in-vitro, in-vivo and in-silico bioactivity tests.  The micro and macro-nutrients content of ethyl acetate fraction of acetonic extract of C. suaveolens bulb and root were assessed by atomic absorption spectroscopic method. The in-vitro antioxidant property of the extract was assessed by following the ABTS, DPPH, and H2O2 radical scavenging assays. The antidiabetic property of the extract was evaluated using the Alpha-Amylase Inhibitory Assay by DNSA and SI method, while the cytotoxic property was assessed using the brine shrimp lethality bioassay. Thrombolytic activity by clot-lysis and anthelmintic activity were assessed. In-vivo antidiarrheal activity by castor oil-induced diarrhea and castor oil-induced intestinal motility (charcoal marker) tests were performed; for antidepressant activity, forced swim and tail suspension tests were performed. Both parts of C. suaveolens possess substantial levels of vital minerals such as calcium, magnesium, phosphorus, sodium, potassium, and copper. The outcomes of our investigation demonstrated that the ethyl acetate fraction of C. suaveolens acetonic extract showed promising and significant antioxidant activity. The half-maximal inhibitory concentration (IC50) values ranged from 8.43 to 520.29 µg/mL for the bulb extract, and from 47.65 to 195.77 µg/mL for the root extract, in ABTS, DPPH, and H2O2 radical scavenging assays respectively. In terms of antidiabetic activity, both the bulb and root extracts showed moderate activity in the Alpha-Amylase Inhibitory Assay by DNSA and SI method. The cytotoxicity of both extracts was found to be significantly toxic. In-vitro thrombolytic activity was not significant compared to standard streptokinase. Anthelmintic activity of both extracts was found to be significant, and root is more significant than bulb. Both extracts have no antidiarrheal effect, but it may produce diarrheal or laxative effects. No significant antidepressant activity is produced by either extract. Based on the findings, it is evident that the ethyl acetate fraction derived from the acetonic extract of C. suaveolens exhibits remarkable pharmacological potential in various in-vitro, in-vivo and in-silico study models. This orchid may be a good source of antioxidant, antidiabetic, and laxative drugs in the future. Therefore, it has the potential to serve as a viable source for isolating a lead compound to treat a multitude of disorders and can be used as a nutritional supplement.